Model Perkembangan Kognitif dalam Penguasaan Keterampilan Membaca Huruf Hijaiyyah pada Anak Usia Dini - Hermansyah, Yudisthira Ade; Mustofa, Muhamad Arif (Edu Journal Innovation in Learning and Education, 2024)
Early childhood children experience rapid cognitive development, and understanding the stages helps teachers, parents, and educators create learning approaches that suit their developmental level. Meanwhile, in the context of the Muslim community, the skill of reading hijaiyyah letters (Arabic letters) is a fundamental first step in understanding Arabic and reading the Koran. Reading hijaiyyah letters is the foundation that allows children to develop a further understanding of the Arabic language and the Islamic religion. This research is an analysis of children's cognitive development in their learning process to master the skill of reading hijaiyyah letters using the literature review method. This research produces stages for mastering the skill of reading hijaiyyah letters, namely: The first stage is the introduction of hijaiyyah letters by recognizing letter shapes and their names. Stage two is to expand their understanding by recognizing simple words consisting of Hijaiyyah letters. that they have learned to understand the concept of words as a series of letters that form meaning. And finally, children are introduced to reading signs, such as vowels, which influence how letters are read in words. The stages of learning to read Hijaiyyah letters in early childhood are a tiered process that combines understanding of letters, words, and spelling in Arabic